Direct Oxidative Arylation of Aryl CH Bonds with Aryl Boronic Acids via Pd Catalysis Directed by the N, N‐Dimethylaminomethyl Group. Issue 4 (21st January 2015) - Zhang, Ji‐Cheng; Shi, Jiang‐Ling; Wang, Bi‐Qin; Hu, Ping; Zhao, Ke‐Qing; Shi, Zhang‐Jie
Abstract: Biaryl skeletons were directly constructed via palladium‐catalyzed ortho ‐arylation of N, N ‐dimethyl benzylamine with aryl boronic acids with high efficiency and high regioselectivity under open‐flask conditions. The N, N ‐dimethylaminomethyl group was first applied as a directing group in such an oxidative coupling. Various substrates proved to be efficient coupling partners, furnishing the corresponding ortho ‐monoarylated or ‐diarylated arenes in moderate to good yields under mild conditions. Abstract : Getting the skeleton right : Biaryl skeletons were directly constructed via palladium‐catalyzed ortho ‐arylation of N, N ‐dimethyl benzylamine with aryl boronic acids under open‐flask conditions. The N, N ‐dimethylaminomethyl group was first applied as a directing group in such an oxidative coupling. Various substrates proved to be efficient coupling partners, furnishing the corresponding ortho ‐monoarylated or ‐diarylated arenes in moderate to good yields under mild conditions.